STUDIES ON LARVAL TREMATODES OF GANGAPUR PROJECTGODAVARI RIVER: DISTOME CErCARIAE: Life Science-Zoology - A.D. GAUTAM; V.R.KAKULTE (International Journal of Life Science and Pharma Research, 2014)
The earlier work on the snails and cercariae of this region was carried out by Karyakarte and Yadav (1974 to 1979) under PL. 480 Project on Control of Molluscan Agents of Helminth Parasites of Agricultural and Veterinary Importance ( Project no. A-7- ADP-39) the account of their findings was published in the year 1981. They examined eight species of snails, viz. Vivparous bengalensis, Melanoides tuberculatus, Melania scabra Lymnea acuminata, Lymnea auricularia, Lymnea luteola, Indoplanorbis exustus Anisus (Gyrulus) convexiusculus. Out of these eight species they reported cercarial infection in six species of snails and the two species.M. scabra and V. bengalensis were free from larval infection. Their work included description of eleven species of freshwater cercariae belonging to Monostome Amphistome and Distome groups The work on larval trematodes was further continued in this region in the Trematology Laboratory and in all nineteen cecariae were collected and described. Out of these cercariae, two ceacarie belonging to Monostome and one belonging to Echinostome group are reported from the same host Melania tuberculata.(1986)Present paper deals with two species of freshwater cercariae which belongs to Distome cercariae. The collection was carried out at Gangapur Project, Godavari River, Darana river, Girnare ponds and ditches around Godavari river. The study is further extended to know various responses of the cercariae to various stimuli such as phototaxis, geotaxis, emrgence and survival of cercariae in various percentage of artificial media.